"Imam Muda" Reality Show: An Analysis Of Non-verbal Communication Of Young Imam - Ainurliza Mat Rahim; Nur Kareelawati Abd. Karim; Mohd Azmir Mohd Nizah; Norazirawati Ahmad (Elixir Organisation, 2024)
Elixir Soc. Sci. 43 (2012) 6898-6904